An interactive strategic analysis framework - Weigelt, Keith; MacMillan, Ian C. (Strategic Management Journal, 1988)
A framework is presented that helps managers systematically evaluate strategic alternatives. We empirically illustrate how to use the framework, and show how changes in beliefs about environmental factors affect the payoffs of specified strategic alternatives.